Scientific authorship, pluralism, and practice. (19th May 2018) - Moffatt, Barton
ABSTRACT: In this article, I argue that understanding authorship requires that we grapple with the plurality of distinct accounts of scientific authorship. As a result, we should be careful in how we identify and quantify unethical practices such as ghostwriting. Judgements about who should be able to decide who is an author raise interesting questions about the autonomy of scientific practices.